2009
DOI: 10.1121/1.3081396
|View full text |Cite
|
Sign up to set email alerts
|

Increase in voice level and speaker comfort in lecture rooms

Abstract: Teachers often suffer from health problems related to their voice.These problems are related to their working environment, including the acoustics of the lecture rooms. However, there is a lack of studies linking the room acoustic parameters to the voice produced by the speaker.In this pilot study, the main goals are to investigate whether objectively measurable parameters of the rooms can be related to a increase of the voice sound power produced by speakers and to the speakers subjective judgments about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 9 publications
(4 reference statements)
3
48
2
Order By: Relevance
“…The importance of the indirect component of one's own voice (also referred to as reflected sound), which is produced after the reflections of one's own voice at the room boundaries, is judged with two alternative measures introduced by Brunskog et al: 17 The room gain and the voice support. It is assumed that the airborne-direct sound reaching the ears has energy E D and that the reflected sound has energy E R .…”
Section: Room Gain and Voice Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of the indirect component of one's own voice (also referred to as reflected sound), which is produced after the reflections of one's own voice at the room boundaries, is judged with two alternative measures introduced by Brunskog et al: 17 The room gain and the voice support. It is assumed that the airborne-direct sound reaching the ears has energy E D and that the reflected sound has energy E R .…”
Section: Room Gain and Voice Supportmentioning
confidence: 99%
“…16 In the presence of low background noise, speakers modify their voice power in different acoustic environments. 17,18 Other studies have also reported an effect of classroom acoustics on teachers' voices, 19,20 and there is a concern that excessive absorption may overdamp the voice of the speaker. 21 Therefore, the classroom acoustics conditions for speakers should also be taken into account during the design of schools.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Room acoustics was pointed out as one of the causes leading to voice problems. Moreover, a link was found between the voice power level used by a talker in a room and the amplication that a room produces on his voice at his own ears, in the presence of low noise levels [12,13]. This eect is related to the Lombard reex (increase of voice power level of a talker in the presence of noise) [14] and the café eect [15] (which is related to the inuence of the acoustic absorption in a room with several talkers on the voice power levels used by them; a decrease in absorption increases the energy of the reverberant eld and thus the sound pressure levels, which in turn lead the talkers to raise their voices due to the Lombard eect).…”
Section: Installationsmentioning
confidence: 99%
“…For this calculation, it is assumed that there are no obstacles closer than 1 m to the measurement device. If there would be, the direct sound should be derived from calibrated measurements in an anechoic chamber, as in [12]. ST V is minimum (ideally approaching −∞ dB) in free-eld, where there is no reected sound, and becomes higher the smaller the room and the higher the reverberation time.…”
Section: Voice Supportmentioning
confidence: 99%